Internationally Adopted Children from Non-European Countries: General Development during the First Two Years in the Adoptive Family - Monica Dalen; Steinar Theie (The Scientific World Journal)
Internationally adopted children are often delayed in their development and demonstrate more behaviour problems than nonadopted children due to adverse preadoption circumstances. This is especially true for children adopted from Eastern European countries. Few studies have focused on children adopted from non-European countries. This paper presents results from an ongoing longitudinal study of 119 internationally adopted children from non-European countries during their first two years in Norway. Several scales measuring different aspects of the children’s development are included in the study: communication and gross motor development, temperamental characteristics, and behaviour problems. The results show that internationally adopted children are delayed in their general development when they first arrive in their adoptive families. After two years the children have made significant progress in development. However, they still lag behind in communication and motor skills compared to non-adopted children. The temperamental characteristics seem very stable from time of adoption until two years after adoption. The children demonstrate a low frequency of behaviour problems. However, the behaviour problems have changed during the two years. At time of adoption they show more nonphysically challenging behaviour while after two years their physically challenging behaviour has increased.